ANALYSIS OF CONJUNCTIONS ON “JIMMY FALLON THE TONIGHT SHOW WITH GIGI HADID” - Dwina Putri Ayu Saragih; Gaguk Rudianto (IKIP Siliwangi, 2024)
Discourse is the practical application of language in particular contexts of society, whereas language is the mechanism of communication that humans apply to communicate meaning.Conjunction is a cohesive device that is not solely focused on the semantics of grammar, claim (Halliday and Hasan, 1976). linguistic components that appear sequentially but unrelated to other, structural ways. Several types will be discussed such as Additive, adversative, causal, and temporal are the different forms of conjunctions. The design of This research, the researcher used descriptive qualitative because This research using sentences and there is no calculation in them, this research is also in the form of paragraphs, so the researcher uses a qualitative method. This study focuses on the functions of conjunctions in sentences in Jimmy Fallon The tonight show with Gigi Hadid. The researchers used check list to collect the data observation method. Result and Discussion 1. Additive 2. Adversative 3. Causal Conjunctions serve as links between individual words, phrases and sentences. Additive, temporal, causal, and adversative are the four conjunctions identified in this study. These conjunctions function to join comparable words, combine sentences with related contexts, and connect sentences in paragraphs.